1994
DOI: 10.1289/ehp.94102548
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in the Umbilical Cord: Implications for Risk Assessment for Minamata Disease.

Abstract: Umbilical cord tissue was obtained from 50 births in the Faroe Islands, where high mercury intake is due to ingestion of pilot whale meat. The mercury concentration correlated significantly with the frequency of maternal whale meat dinners during pregnancy and with mercury concentrations in umbilical cord blood and in maternal hair. The results were compared with published values for mercury in umbilical cord tissue from 12 infants diagnosed with congenital methylmercury poisoning in Minamata, Japan. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 8 publications
(6 reference statements)
1
18
0
Order By: Relevance
“…Also, it has been demonstrated that the mercury concentration in the umbilical cord tissue was well associated with the mercury concentration in cord blood (r s =0.85), rather than that in maternal hair (r s =0.77) (Dalga˚rd et al 1994). On the other hand, Japanese maternal hair mercury levels in this study could explain only 18% of the variation of prenatal exposure (r s =0.42).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been demonstrated that the mercury concentration in the umbilical cord tissue was well associated with the mercury concentration in cord blood (r s =0.85), rather than that in maternal hair (r s =0.77) (Dalga˚rd et al 1994). On the other hand, Japanese maternal hair mercury levels in this study could explain only 18% of the variation of prenatal exposure (r s =0.42).…”
Section: Discussionmentioning
confidence: 99%
“…Given the conversion equation developed by Akagi et al (1998), i.e., [Maternal-hair T-Hg concentration at parturition (μ g/g)] = 25.24 × [MeHg concentration in dry cord tissue (μ g/g)], the maximum value (i.e., 0.37 μ g/g) of MeHg concentration in dry cord tissue as shown in Table 3 was estimated to be 9.3 μ g/g of maternal-hair T-Hg concentration, which would be near the critical concentration of MeHg affecting the nervous system function asymptomatically (National Research Council 2000;Murata and Dakeishi 2005). In the Faroese birth cohort study, while T-Hg concentrations in cord blood and in maternal hair at parturition (range, 0.2 ~ 39.1 μ g/g) TABLE TABLE T were employed for the risk assessment of MeHg neurotoxicity (Grandjean et al 1997(Grandjean et al , 2001Sørensen et al 1999;Murata et al 1999bMurata et al , 2004aDebes et al 2006), the exposure assessment was made using the freeze-dry umbilical cord in addition to the former two samples (Dalgård et al 1994;Grandjean et al 2005).…”
Section: Mercury Concentrations In Cord Tissuementioning
confidence: 99%
“…After reading the article, Dr. Robert W. Miller of the U.S. National Cancer Institute (1976) submitted a short letter entitled "Dried human umbilical cords and study of pollutant" to the Lancet and gave the two researchers full marks for the usefulness of dry umbilical cord, describing that cords systematically collected and stored might be used as a biological dosimeter for changes in the levels of pollutants over time. Since then, mercury concentrations in cord blood and tissue, which are part of the fetus, have been employed as fetal biomarkers of hazardous substances (Dalgård et al 1994;Grandjean et al 1997;Nakai et al 2004).…”
mentioning
confidence: 99%
“…Also, it has been suggested that a myth that hair mercury concentration reflects the methylmercury concentration circulating in the blood may collapse if a study population includes subjects with artificial hairwaving . The mercury level in the umbilical cord tissue has been reported to be associated well with that in cord blood (Dalga˚rd et al 1994), and most Japanese families treasure a small piece of the umbilical cord of the child as a birth memento (Akagi et al 1998). For this reason, we tried to collect dry umbilical cord samples of the children from parents who participated in our study.…”
Section: Introductionmentioning
confidence: 99%